An electrochemical sensor based on a MOF/ZnO composite for the highly sensitive detection of Cu(ii) in river water samples. Issue 9 (10th February 2022) - Li, Zhenshan; Li, Qi; Jiang, Rong; Qin, Yan; Luo, Yan; Li, Jinsong; Kong, Wei; Yang, Zhiguo; Huang, Chao; Qu, Xin; Wang, Tao; Cui, Lin; et al.
Abstract : Cu(ii ) ions are one of the most common forms of copper present in water and can cause bioaccumulation and toxicity in the human body; therefore, sensitive and selective detection methods are required. Abstract : Cu(ii ) ions are one of the most common forms of copper present in water and can cause bioaccumulation and toxicity in the human body; therefore, sensitive and selective detection methods are required. Herein, a copper ion sensor based on a UiO-66-NH2 /ZnO composite material is proposed. The UiO-66-NH2 /ZnO nanocomposite was prepared by an ultrasonic mixing method. The morphology and structure of the nanocomposite were studied by scanning electron microscopy (SEM), transmission electron microscopy (TEM) and X-ray diffraction (XRD). The sensitivity to Cu(ii ) is 6.46 μA μM −1 and the detection limit is 0.01435 μM. The composite material is rich in –OH and –NH2 groups, which are active sites for Cu(ii ) adsorption. The UiO-66-NH2 /ZnO-modified electrode has good repeatability and anti-interference ability. The sensor was successfully used for the determination of Cu(ii ) in an actual water sample.